Reactive infectious mucocutaneous eruption: An uncommon dermatological manifestation of Mycoplasma pneumoniae: a case report - Sobika, S.; Suganthan, N.; Brammah, R.T.; Sathiyareka, S.; Malaravan, M. (Teaching Hospital Jaffna, Sri Lanka, Department of Medicine, Faculty of Medicine, University of Jaffna, Sri Lanka, 2025)
Mycoplasma pneumoniae is a common respiratory pathogen that causes a wide range of clinical manifestations, from mild upper respiratory tract infections to severe atypical pneumonia. Besides its pulmonary involvement, it can cause several extrapulmonary complications. Among these, dermatological manifestations such as Stevens-Johnson syndrome, erythema multiforme, and toxic epidermal necrolysis are well recognised. Reactive infectious mucocutaneous eruption is a relatively rare but notable manifestation. This case report describes a 35-year-old man who developed mucosal lesions involving the ocular, oral, and genital areas after a prodrome of respiratory symptoms. Laboratory tests confirmed a high antibody titre of Mycoplasma pneumoniae. While initial antibiotic therapy improved the respiratory symptoms, mucosal involvement persisted, necessitating the use of systemic corticosteroids, which led to a significant clinical improvement. This case highlights the importance of timely recognition and correct management of this uncommon manifestation of mycoplasma infection.
Keywords: Mycoplasma pneumoniae; Reactive infectious mucocutaneous eruption; Stevens-Johnson Syndrome; Erythema multiforme; Mycoplasma pneumoniae-induced rash and mucositis